ENHANCING FIREFIGHTER SAFETY: EVALUATING PPE FOR COMFORT AND EFFECTIVENESS - Ticlo, Tahira; Rao, Roopa (International Journal of Research -GRANTHAALAYAH, 2024)
Exploratory research was conducted among 160 firefighters from two Indian states - Goa and Maharashtra, to evaluate the ergonomic aspects of Personal Protective Equipment (PPE) and Clothing, focusing on firefighter comfort and operational effectiveness. Using a validated self-constructed questionnaire, researchers conducted structured interviews with firefighters to gain insights into the strengths and limitations of current PPE designs. The study revealed critical gaps in PPE utilization, informing recommendations for precise improvements to enhance firefighter safety and operational efficiency during emergencies. These findings aim to improve training programs and protocols, ensuring firefighters are not exposed to high-risk temperatures without adequate PPE. The study's results can influence policy decisions and research resource allocation, ensuring optimal equipping of firefighters to handle diverse hazards safely and comfortably. The research has broader implications, aiming to drive advancements in PPE materials and technologies, focusing on ergonomics, thus benefiting firefighting practices globally. By prioritizing comfort and functionality in PPE design, the study seeks to enhance the overall well-being and performance of firefighters in hazardous environments. Ultimately, the study aspires to inform better training programs, strengthen disaster response capabilities, and shape policies that prioritize firefighter safety worldwide, contributing to improved public safety on a global scale.